MERDEKA CURRICULUM FOR ELEMENTARY ENGLISH LEARNING IN MLATI SLEMAN - Olam, Rismalla Ma’im (Cendikia: Jurnal Pendidikan dan Pengajaran, 2024)
The Merdeka Curriculum commenced implementation in elementary schools (SD) in the 2021/2022 academic year. The Merdeka Curriculum should reintroduce English language instruction as an option in primary education. This study seeks to understand the execution of the English language learning component of the Merdeka Curriculum in primary schools in Mlati and to identify the issues faced by teachers in teaching English under this curriculum. Mlati has 38 primary schools, and the samples collected reflect all of these institutions. There were two public elementary schools and two private elementary schools. For the study, four instructors and eight students from four primary schools provided data. This study employed a descriptive-qualitative methodology. The Merdeka Curriculum promotes autonomous learning in primary schools, as indicated by the statistics collected. The Merdeka Curriculum had a highly positive influence on both educators and learners. Educators exhibit increased creativity and innovation, while students experience a conducive learning environment due to the engaging nature of the class. Numerous challenges arose, including the pupils' disparate motivation and writing proficiency, insufficient training and knowledge of the Merdeka Curriculum for English educators, and the instructor's excessive reliance on many texts, which hindered instructional focus.